Measuring Induced Travel Elasticities associated with Local Roads from Trip Generation - Robert B. Noland (Findings)
Induced travel elasticities associated with new road capacity are typically estimated for roads of higher functional classifications, such as interstate freeways and principal arterials. These are estimated as “own” elasticities, that is an increase in lane kilometers of a given type of road leads to increased vehicle-km of travel (VKT) on that same road type. What are the elasticities associated with local roads, specifically those associated with roads for a new residential development? This question is addressed by calculating the trips generated from a development assuming different levels of trips generated from each residence. In this example, the development includes 4.32 new lane-kms of local roads. Total VKT to exit the development is calculated and the calculated VKT and amount of new lane-kms are used to estimate an implied elasticity using county-level local road lane-km and VKT data from both the States of New Jersey and Maryland. Findings suggest an induced travel elasticity for local roads generally less than for higher functional road categories but also highly dependent on the household trip generation rate.